Laporan Kasus: Seorang Penderita dengan Kecurigaan Rabies - Ayu Ria Widiani, Gusti; Mahardika Yasa, I Made (Lembaga Pengembangan Kinerja Dosen, 2022)
Rabies is a zoonotic disease that can attack the central nervous system and can be fatal because it can cause death. Rabies is caused by an RNA virus of the genus Lyssavirus in the family Rhabdoviridae and can be transmitted to humans through contact with infected animals, particularly bites and scratches. Most cases (98%) were caused by dog bites and the rest by other animals such as monkeys and cats. This disease has a very poor prognosis, but can be prevented by vaccination. Rabies virus is a neurotrophic virus that can infect humans and cause fatal encephalitis. The purpose of this paper is to provide information on rabies cases, prevention, early symptoms to watch out for, and emergency management. A 45-year-old man has clinical encephalitis with suspected viral EC with suspected rabies dd/non-specific viral dd bacterial. Patients complain of not being able to swallow and afraid of water, restlessness, hypersalivation, patients are sensitive to sound, shortness of breath, difficulty swallowing, fear of wind, patients want to bite and hydrophobia, aerophobia and hypersalivation. Therapy in cases of rabies is to provide supportive care and isolation treatment. The prognosis for rabies patients is generally poor, because mortality can reach 100% after the rabies virus reaches the central nervous system, death from respiratory/cardiac arrest most often occurs within 2-3 days after the onset of rabies symptoms. After being bitten by an animal suspected of being rabid, cleaning the wound, administering VAR and SAR is an effective preventive measure against the transmission of the rabies virus.